The Relationship Between D-Dimer and NLR With the Clinical Severity of Pneumonia in Covid-19 Patients at the Regency Hospital Sidoarjo Period of June to August 2021. - Retno Arimbi, Muzaijadah; Tri Ratnasari, Diana; Sri Wulandari, Atik; Devina, Elita; Irawan, Atok (Journal of Neonatal Surgery, 2025)
COVID-19 has a wide range of severity categorized ranging from asymptomatic to critical symptoms, with varying clinical indicators such as pneumonia and hypoxia. This severity can be predicted using a variety of parameters, including neutrophil-to-lymphocyte ratio (NLR) and D-dimer levels, which are important prognosis markers in assessing disease progression. This study aims to determine the relationship between NLR and D-dimer with the clinical severity of pneumonia in COVID-19 patients at Sidoarjo Regency Hospital in the period of June to August 2020. The research method used is observational using secondary data from the electronic medical records of Sidoarjo Regency Hospital. Data analysis was carried out using the Kruskal-Wallis statistical test. The study population included all patients diagnosed with pneumonia due to COVID-19 and treated at Sidoarjo Regency Hospital, while the sample included patients who had complete data for NLR and D-dimer.